Trends in the use of information and communication technologies in the teaching of foreign languages and translator training - N. Kovalchuk (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The article provides a comparative analysis of 27 studies carried out over the last five years on the use of information and communication technologies (ICT) in education, the application of ICT in education and the utilisation of machine translation (MT) in the teaching of foreign languages and translation. It outlines the trends identified by these studies, the achievements to date and the most promising areas for further research. The main areas identified were: the theoretical justification for the use of ICT; the comparative effectiveness of different MT systems, on the one hand, and human translators, on the other; the assessment of students’ target texts taking into account their degree of independence from MT; the role of post-editing in the teaching of foreign languages and translation and the methodology of its application in the teaching process; the role of ICT in the translation industry and its impact on the content of training programmes and curricula for future translators. The analysis showed that there is a considerable lack of sufficient research in the first area, as well as contradictory results in the remaining three (discrepancies in the evaluation of the translation efficiency of different MT systems and of MT compared to humans; unavailability of an effective and economical methodology for the evaluation of texts produced with the use of MT; the absence of a rational methodology for the application of post-editing at different stages of training and under different conditions). The author highlights the positive attitude of the translation industry towards ICT and the significant gap between its needs and the content of the training of future translators. The most promising directions for further research are outlined. These include, in particular: developing a methodology for the formation of skills included in the model of technological competence of a future translator; clarifying the comparative effectiveness of different MT systems and their potential areas of application; specifying the differences between machine and human translation and determining their optimal correlation in translator training and translation practice; identifying the optimal proportion of MT in the content of translator training and ways of evaluating texts translated using MT; developing a model for the effective integration of post-editing into the content of training; investigating ways of increasing the influence of the translation industry on the content of translator training.